Development of Flash Flood Mitigation Problem with Sustainable Auto-Drainage System - Muhammad Aqim Mohammad Saimi; Rohaida Hussain (Journal of Engineering Technology, 2022)
Floods are natural phenomena that occur every year in Malaysia during the monsoon season which runs from November to January. Despite the fact that various steps have been taken, it appears to have remained unsolved. Here, the auto-drainage system to mitigate flash flood is proposed to improve the drainage system as it is one of the major reasons that caused the flood. This project is the first phase of the flash flood mitigation system where it provides crucial information such as water level in the drainage system, the plan and the preparation to the public as well as the local authorities. Auto-drainage system offers continuous monitoring on the water level in drainage system and allows water to divert into alternative drainage during critical times. There are 3 different levels of warning; low, medium and high. During low level, the water pump is in idle mode or in a safe zone. When the water reaches medium, the pump will start to divert the water into an alternative drainage system. At high level, the pump will continue to divert the water the notification to evacuate the area is despatched. The test run gives a positive result and fulfills all the objectives in effort to mitigate the flash flood.